The Dynamics of Stock Index and Stock Index Futures Returns - Stoll, Hans R.; Whaley, Robert E. (Journal of Financial and Quantitative Analysis, 1990)
In rational, efficiently functioning markets, the returns on stock index and stock index futures contracts should be perfectly, contemporaneously correlated. This study investigates the time series properties of 5-minute, intraday returns of stock index and stock index futures contracts, and finds that S&P 500 and MM index futures returns tend to lead stock market returns by about five minutes, on average, but occasionally as long as 10 minutes or more, even after stock index returns have been purged of infrequent trading effects; however, the effect is not completely unidirectional, with lagged stock index returns having a mild positive predictive impact on futures returns.